Diseño de ambientes de aprendizaje para el desarrollo de la creatividad en niños de educación inicial de la Unidad Educativa Francisco Huerta Rendón - Muñoz Valarezo, Hillary Ghyslaine (2023)
The learning environments for the development of creativity in early childhood education are those physical and social spaces that encourage the stimulation and promotion of creativity in children at an early age. These environments should be designed so that children can interact with different materials and objects, experiment with them and develop their imagination and creativity.